TI_GERICHTE 12.2014.73 vom 16. Februar 2015 , Riconscimento ed exequatur di sentenza straniera - motivi di diniego - TI Tribunale d'appello (2015)
Riconscimento ed exequatur di sentenza straniera - motivi di diniego